Geopolitics of Renewable Energy: Shaping the Global Power Landscape - Mangla , Ashima (Gyan Management Journal, 2023)
This research paper provides a comprehensive analysis of the geopolitical  implications of the global transition towards renewable energy. It  scrutinizes the traditional energy landscape, emphasizing how fossil fuel  resources have historically shaped geopolitical power structures. The key  drivers of the shift towards renewables, such as climate change, economic  viability, and energy security, are elaborated. The paper identifies emerging  leaders in the renewable sector, namely, China and the European Union,  and discusses how their strategic positioning could reshape global power  dynamics. It examines the potential challenges associated with this energy  transition and strategies to mitigate these challenges, emphasizing the  role of international cooperation. The paper concludes that the renewable  energy revolution marks a significant shift in global geopolitics. This  research underscores the deep interconnection between energy and power,  emphasizing its enduring relevance in this renewable future.
Keywords: Geopolitics; Renewable Energy; Global Power Landscape; Fossil Fuels; Climate Change; Energy Security